Does larval food availability ultimately select for seasonal reproduction in marine invertebrates with feeding larvae? A field test of Crisp’s Rule with the temperate sea star Pisaster ochraceus - Lawrence V. Basch; John S. Pearse (Marine Ecology, 2022)
Most organisms reproduce seasonally, including most species of marine invertebrates that live across wide ranges in habitat, depth and environmental conditions. We asked: What ultimately selects for seasonal reproduction in benthic marine invertebrates with planktotrophic larvae (characteristic of ≥70% of marine invertebrates)? We hypothesized that seasonal variation in food available for the larvae ultimately selects for timing of adult reproduction. Testing this hypothesis requires a whole life cycle perspective and approach. Using a known proximate cue, daylength, we shifted gametogenesis in the laboratory by six months in a seasonally breeding temperate sea star, the Ochre Star Pisaster ochraceus (Brandt 1835). We were then able to induce spawning, fertilize gametes and culture resulting embryos in vitro to produce feeding larvae six months out of phase with natural photoperiod. We field‐reared these out‐of‐season larvae, similarly produced in‐season conspecifics and similar larvae of an aseasonally breeding asteroid, the Bat Star Patiria miniata (Brandt 1835) in mesh‐covered flow‐through containers that were deployed in seasonally contrasting oceanographic conditions reflecting different productivity regimes and larval food availability in spring and fall. Larval development and survival were similar between seasons: for example, planktonic larval duration was 48 d to first metamorphosis in spring vs. 45 d in fall for P. ochraceus . Hence, temporal variation in available phytoplankton may not be an ultimate selection factor acting on these larvae to regulate timing of seasonal reproduction in the adults. Alternatively, in this and other species of marine invertebrates, selection acting on early benthic juveniles or other life stages may determine the timing of adult reproduction.

Origin of pyroxenites in the oceanic mantle and their implications on the reactive percolation of depleted melts - V. Basch; Elisabetta Rampone; G. Borghini; C. Ferrando; A. Zanetti (Contributions to Mineralogy and Petrology, 2019)

Half a century (1954–2009) of dissection data of sea urchins from the North American Pacific coast (Mexico–Canada) - T. A. Ebert; J. C. Hernández; S. Clemente; M. P. Russell; L. V. Basch; R. A. Boolootian; P. M. Detwiler; M. C. Kenner; A. L. Lawrence; J. M. Lawrence; D. L. Leighton; J. S. Palleiro; et al. (Ecology, 2013)
Total body size, mass or linear measurements, and gonad mass or volumes have been recorded for the North American Pacific coast sea urchins Strongylocentrotus purpuratus, Mesocentrotus (Strongylocentrotus) franciscanus, and Lytechinus pictus by various workers at diverse sites and for varying lengths of time from 1954 to 2009. Some dissections included other body components such as the gut, body wall, and Aristotle's lantern, and some dissections included both wet and dry mass. There are numerous peer‐reviewed publications that have used some of these data, but some data have appeared only in graduate theses or in the gray literature. There also are data that have never appeared outside the original data sheets. Historically, data were used to describe reproductive cycles and then to compare responses to stressors such as food limitation or pollution. Differences in temperature among sites also have been explored. More recently, dissection data have linked gonad development to ocean conditions, so called bottom‐up forcing. The data set presented here is a historical record of gonad development for a common group of marine invertebrates in intertidal and nearshore environments, which can be used to test hypotheses concerning future changes associated with climate change and ocean acidification along the Pacific Coast of North America.